Estradiol Increases the Sensitivity of Hippocampal CA1 Pyramidal Cells to NMDA Receptor-Mediated Synaptic Input: Correlation with Dendritic Spine Density - Woolley, Catherine S. (J Neurosci, 1997)
Previous studies have shown that estradiol induces new dendritic spines and synapses on hippocampal CA1 pyramidal cells. We have assessed the consequences of estradiol-induced dendritic spines on CA1 pyramidal cell intrinsic and synaptic electrophysiological properties. Hippocampal slices were prepared from ovariectomized rats treated with either estradiol or oil vehicle. CA1 pyramidal cells were recorded and injected with biocytin to visualize spines. The association of dendritic spine density and electrophysiological parameters for each cell was then tested using linear regression analysis. We found a negative relationship between spine density and input resistance; however, no other intrinsic property measured was significantly associated with dendritic spine density. Glutamate receptor autoradiography demonstrated an estradiol-induced increase in binding to NMDA, but not AMPA, receptors. We then used input/output (I/O) curves (EPSP slope vs stimulus intensity) to determine whether the sensitivity of CA1 pyramidal cells to synaptic input is correlated with dendritic spine density. Consistent with the lack of an estradiol effect on AMPA receptor binding, we observed no relationship between the slope of an I/O curve generated under standard recording conditions, in which the AMPA receptor dominates the EPSP, and spine density. However, recording the pharmacologically isolated NMDA receptor-mediated component of the EPSP revealed a significant correlation between I/O slope and spine density. These results indicate that, in parallel with estradiol-induced increases in spine/synapse density and NMDA receptor binding, estradiol treatment increases sensitivity of CA1 pyramidal cells to NMDA receptor-mediated synaptic input; further, sensitivity to NMDA receptor-mediated synaptic input is well correlated with dendritic spine density.